Fruit waste: a current perspective for the sustainable production of pharmacological, nutraceutical, and bioactive resources - Sha, Shankar Prasad; Modak, Debabrata; Sarkar, Sourav; Roy, Sudipta Kumar; Sah, Sumit Prasad; Ghatani, Kriti; Bhattacharjee, Soumen (Frontiers in Microbiology, 2023)
Fruits are crucial components of a balanced diet and a good source of natural antioxidants, that have proven efficacy in various chronic illnesses. Various kinds of waste generated from fruit industries are considered a global concern. By utilizing this fruit waste, the international goal of "zero waste" can be achieved by sustainable utilization of these waste materials as a rich source of secondary metabolites. Moreover, to overcome this waste burden, research have focused on recovering the bioactive compounds from fruit industries and obtaining a new strategy to combat certain chronic diseases. The separation of high-value substances from fruit waste, including phytochemicals, dietary fibres, and polysaccharides which can then be used as functional ingredients for long-term health benefits. Several novel extraction technologies like ultrasound-assisted extraction (UAE), pressurized liquid extraction (PLE), and supercritical fluid extraction (SFE) could provide an alternative approach for successful extraction of the valuable bioactives from the fruit waste for their utilization as nutraceuticals, therapeutics, and value-added products. Most of these waste-derived secondary metabolites comprise polyphenols, which have been reported to have anti-inflammatory, insulin resistancetreating, cardiovascular disease-maintaining, probiotics-enhancing, or even anti-microbial and anti-viral capabilities. This review summarizes the current knowledge of fruit waste byproducts in pharmacological, biological, and probiotic applications and highlights several methods for identifying efficacious bioactive compounds from fruit wastes.